1984
DOI: 10.1177/07399863840061003
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Behavioral Science Research: Recommendations for Future Research

Abstract: This article briefly presents the major developments in Hispanic behavioral science research over the past decade and provides recommendations for future research. Some of the major research-related developments have emanated largely from three research centers dedicated to the study of Hispanic mental health, a national organization of service providers, and a minority mental health fellowship program. Numerous individuals from various backgrounds were consulted about future research directions. The salient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…While many recent studies have investigated femininity and masculinity, most of these focused on white middle-class women. The literature on Hispanic women is limited (Espin and Warner, 1982;Padilla and Lindholm, 1984;Pugh and Vazquez-Nuttall, 1983;Rosario, 1982;Torres-Matrullo, 1980). The best known of the several instruments designed to measure masculinity, femininity, and androgyny (individuals high in both traits) that have been used with Hispanics are the Bem Sex Role Inventory [BSRI] (Bern, 1974) and the Personal Attributes Questionnaire [PAQ] (Spence, Helmreich, & Stapp, 1974).…”
Section: Studies Of Femininity and Masculinity And Attitudes Toward Wmentioning
confidence: 99%
“…While many recent studies have investigated femininity and masculinity, most of these focused on white middle-class women. The literature on Hispanic women is limited (Espin and Warner, 1982;Padilla and Lindholm, 1984;Pugh and Vazquez-Nuttall, 1983;Rosario, 1982;Torres-Matrullo, 1980). The best known of the several instruments designed to measure masculinity, femininity, and androgyny (individuals high in both traits) that have been used with Hispanics are the Bem Sex Role Inventory [BSRI] (Bern, 1974) and the Personal Attributes Questionnaire [PAQ] (Spence, Helmreich, & Stapp, 1974).…”
Section: Studies Of Femininity and Masculinity And Attitudes Toward Wmentioning
confidence: 99%
“…Although it has been suggested that perceived membership in both ethnic and mainstream groups may be best to reduce conflict and adjustment problems (Padilla & Lindholm, 1984;Rogler, Cortes, & Malgady, 1991), researchers have often failed to operationalize ethnic identification as a bidimensional phenomenon (Rotheram-Borus, 1990). In contrast to the ethnic identification domain, acculturation research has recognized the need to consider the degree of immersion into both alternative and native cultures (Berry, 1980;Berry, Trimble, & Olmedo, 1986;Mendoza, 1989).…”
mentioning
confidence: 99%
“…Moreover, we echo Padilla and Lindholm (1984) in the quest for future qualitative research within the HJBS to investigate issues and stressors of life span development. Qualitative research is an essential avenue in which one can capture a student's deepest fears and challenges, as well as dreams and aspirations about the college process.…”
Section: Discussionmentioning
confidence: 93%